Design for Manufacturing and Assembly Of Eco-products: Prototyping of Mini 4wd Components Using Polylactic Acid Filament Material - Indro Prakoso; Katon Muhammad; Hasyim Asyari; Reza Azizul Nasa Alhakim; Nabilah Asysyahidah (Engineering Faculty, UNSOED, 2025)
This research focuses on the design and production of eco-friendly products using Polylactic Acid (PLA) material for the mini 4WD kit components, utilizing the Design for Manufacturing and Assembly (DFMA) approach. The objective is to reduce plastic waste in toys by replacing conventional plastic materials with biodegradable PLA. The research evaluates the potential of PLA in manufacturing, addressing consumer requirements for speed, durability, and aesthetics. The study highlights how DFMA optimization leads to efficient processes while maintaining the eco-friendly benefits of PLA material. Using additive manufacturing technique by 3D Printer for making 4WD mini kit component we got material filament PLA consumption is 11.81 m and 37.21 g. Time for production running is 8,89 hour for all part and prodcution cost is IDR 159,302. For the future market awarness and consumer purchase interest is to implement a branding strategy that highlights the product’s environmentally friendly attributes. Businesses may create environmentally friendly products that satisfy customer wants while reducing their environmental effect by substituting biodegradable materials like PLA for conventional plastics and streamlining the production process with DFMA. Future studies will keep improving these procedures and investigating novel materials that have even more advantages for sustainability.